2014
DOI: 10.1038/ismej.2014.243
|View full text |Cite
|
Sign up to set email alerts
|

Clay minerals and metal oxides strongly influence the structure of alkane-degrading microbial communities during soil maturation

Abstract: Clay minerals, charcoal and metal oxides are essential parts of the soil matrix and strongly influence the formation of biogeochemical interfaces in soil. We investigated the role of these parental materials for the development of functional microbial guilds using the example of alkane-degrading bacteria harbouring the alkane monooxygenase gene (alkB) in artificial mixtures composed of different minerals and charcoal, sterile manure and a microbial inoculum extracted from an agricultural soil. We followed chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…They allow for insight into fundamental questions about soil aggregate development38, organic matter turnover39 and mineralogical influences on microbial communities and decomposition404142. Here we use model soils for real-time monitoring of microbial-SOM formation and demonstrate that microbial processing of simple C substrates produced an abundance of stable, chemically diverse SOM dominated by microbial proteins and lipids, comparable to natural soils.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They allow for insight into fundamental questions about soil aggregate development38, organic matter turnover39 and mineralogical influences on microbial communities and decomposition404142. Here we use model soils for real-time monitoring of microbial-SOM formation and demonstrate that microbial processing of simple C substrates produced an abundance of stable, chemically diverse SOM dominated by microbial proteins and lipids, comparable to natural soils.…”
Section: Discussionmentioning
confidence: 95%
“…Variations in SOM chemistry with mineralogy have previously been attributed to differences in dominant binding mechanisms and selective adsorption among mineral types5253. However, such differences can also result from divergent microbial communities4041, and thus the production of chemically different microbial SOM compounds43. Indeed, in kaolinite soil both fungal and lipid abundances were greater relative to montmorillonite soil.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies reporting a significant effect of mineral composition such as different clay minerals or Fe oxides on bacterial communities in incubation experiments with artificial soils ( Babin et al, 2013 ; Heckman et al, 2013 ; Vogel et al, 2014 ; Steinbach et al, 2015 ). On the contrary, we detected only a slight soil age effect for bacterial T-RFLP profiles analyzed with HhaI ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 For example, Steinbach et al 24 reported that metal oxides have significant impacts on alkane-degrading community structure and the effects increased during soil maturation. Recently, several studies have examined the effects of soil minerals on the viability of bacterial cells.…”
Section: Introductionmentioning
confidence: 99%